Revealing the functions of novel mutations in RAB3GAP1 in Martsolf and Warburg micro syndromes. Issue 4 (7th February 2019) - Koparir, Asuman; Karatas, Omer Faruk; Yilmaz, Seda Salman; Suer, Ilknur; Ozer, Bugra; Yuceturk, Betul; Ozen, Mustafa
Abstract : Purpose : Martsolf (MS) and Warburg micro syndromes (WARBM) are rare autosomal recessive inherited allelic disorders, which share similar clinical features including microcephaly, intellectual disability, brain malformations, ocular abnormalities, and spasticity. Here, we revealed the functions of novel mutations in RAB3GAP1 in a Turkish female patient with MS and two siblings with WARBM. We also present a review of MS patients as well as all reported RAB3GAP1 pathogenic mutations in the literature. Methods : We present a female with MS phenotype and two siblings with WARBM having more severe phenotypes. We utilized whole‐exome sequencing to identify the molecular basis of these syndromes and confirmed suspected variants by Sanger sequencing. Quantitative (q) RT‐PCR analysis was carried out to reveal the functions of novel splice site mutation detected in MS patient. Results : We found a novel homozygous c.2607‐1G>C splice site mutation in intron 22 of RAB3GAP1 in MS patient and a novel homozygous c.2187_2188delinsCT, p.(Met729_Lys730delinsIleTer) mutation in exon 19 of RAB3GAP1 in the WARBM patients. We showed exon skipping in MS patient by Sanger sequencing and gel electrophoresis. qRT‐PCR analysis demonstrated the reduced expression of RAB3GAP1 in the patient with the c.2607‐1G>C splice site mutation compared to a healthy control individual. Conclusion : Here, we have studied two novel RAB3GAP1 mutations in two different phenotypes; a MS associated novel splice site mutation, and a WARBM1 associated novel deletion–insertion mutation. Our findings suggest that this splice site mutation is responsible for milder phenotype and the deletion–insertion mutation presented here is associated with severe phenotype.